Eros e civilização em Luiz Vilela: a repressão sexual em contos no ambiente escolar - Silva, Janaína Paula Malvezzi Torraca da (2013)
Our goal in this workis to demonstrate, in Luiz Vilela‘s short stories, how is stagedthe roleof the school, as reproductiveinstitution of thestatusquo, as a sexual repressive foundation. Our corpus consists of the tales ―Triste‖ (―Sad‖), ―Depois da aula‖ (―After school‖), ―Com os seus próprios olhos‖ (―With your own eyes‖) and ―Meus anjos‖ (―My angels‖). The theoretical framework use dint he literary works as follows: Eros and civilization: a philosophical inquiry into Freud, by HerbertMarcuse, first published in 1955; Sexual repression: that our(un) known by Marilena Chauí edited in 1984; Two fold flame: love and eroticism, Octavio Paz, published in 1995; Poeticsofspace, Gaston Bachelard, first publishedin 1957;to compose thepsychoanalytic piece of work we used Freud and the unconscious, Luiz Alfredo Garcia-Roza, released in 1984. We ask our selves: How civilization in tales of the author is figured, especially those dealing with eroticism? How this short stories describe sexual repression in society and school? Which is the function of institutional authority to be drawn from these tales, whose topic is eroticism in schools? Which function represents the school in these narratives? Our first hypothesis is that the school, through characters that represents institutional authority, is driven by repressive ideology to eroticism, due to the dominant Christian ideals in society. Another hypothesis that we rose in LuizVilela, is that the eroticism experienced in the school, for children and teens, bare the entrails of a repressive society of Christian ideology. We prove that these elements are configured in tales of Luiz Vilela, showing how the eroticism experienced under the repressive school naked bowels of a society of Christian ideology